Determinan Kinerja Guru di Kabupaten Aceh Utara melalui motivasi sebagai variable intervening - Kussyeri, Kussyeri; Matriadi, Faisal; Ikramuddin, Ikramuddin (Universitas Malikussaleh, 2021)
This study analyzes several variables that affect teacher performance in North Aceh. The variable that wants to be disclosed is Competence. Respondents in this study are 198 junior high school teachers in North Aceh. Leadership, motivation and their influence on teacher performance. The sampling method used is a saturated sample. The data analysis method used is Structural Equation Modeling (SEM) using AMOS 21 software. From the results of the study, it can be seen that the influence of competence on motivation is not significant, the influence of leadership on motivation is very significant. Meanwhile, the influence of competence on teacher performance is also very significant. Likewise, the influence of leadership on teacher performance is also significant. Motivation was also found to mediate the influence between Competence and Leadership on Teacher Performance. It is recommended to improve teacher performance, it is hoped that the leadership or principal of SMP Negeri in North Aceh Regency to improve teacher competence, improve leadership abilities and also increase motivation for teachers so that their performance will increase in the future.